The Semi-Presidential EU Governmental System As A Constitutional Design - KARAYİĞİT, MUSTAFA TAYYAR (ULUSLARARASI ILISKILER KONSEYI DERNEGI, 2020)
The article attempts to depict the governmental system of the EU on the basis of the characteristics of its executive institutions, intra-executive relationships, the relationships between the executive and legislative institutions, and the combination of supranational (the Community method) and intergovernmental nature of decision-making in the post-Maastricht period of European integration. Sui generis characteristics of the EU do not preclude a systemic configuration on the basis of comparative analysis with statal governmental systems. The article asserts that post-Maastricht European integration has led to the gradual establishment of a semipresidential governmental system in the EU. This system accordingly involves particularly on the one hand the deliberative dual-executive authority in the EU, namely the European Council with accumulated prerogatives and the Commission with a subordinated role compared to the dominant position of the European Council, though being subject to legislative scrutiny, or the Council with an occasional executive role in certain fields, and on the other hand the expanded powers of the European Parliament, as the lower house.
Keywords: Dualism; Dual Executive Structure; Semi-Presidentialism; Intergovernmentalism; Supranationalism; EUROPEAN COUNCIL; INTEGRATION; POWERS; SUPRANATIONALISATION; SEPARATION; COMMUNITY; ROLES; MODEL